Research progress of extracellular vesicles in the pathogenesis of type IIIA chronic prostatitis - Cheng, Le; Luo, Peiyue; Li, Wei; Chen, Qi; Gan, Lifeng; Zhang, Fangtao; Zheng, Liying; Qian, Biao (Frontiers in Immunology, 2025)
Chronic prostatitis is a prevalent urological condition that significantly impacts patients’ quality of life. Advances in the study of Extracellular Vesicles (EV) have revealed their close involvement in the pathogenesis of prostatitis. This paper reviews the progress in understanding the role of EV in the pathogenesis of chronic prostatitis type IIIA, particularly their involvement in inflammatory responses, cell signaling, and interactions with immune cells. Additionally, it explores the potential applications of EV as drug delivery vehicles, including the targeted delivery of anti-inflammatory agents and immunomodulators, and highlights the challenges associated with developing exosome-based therapeutic strategies. In-depth research on EV holds promise for offering new insights into the diagnosis and treatment of inflammatory diseases.